2023
DOI: 10.1097/mao.0000000000003801
|View full text |Cite
|
Sign up to set email alerts
|

Hearing After Vestibular Schwannoma Surgery: Is It Preserved Forever?

Abstract: Introduction: Currently, it is possible to preserve the auditory nerve in a large number of cases, but the preservation of the hearing itself is unpredictable. Apart from wait and scan strategy and stereoradiotherapy, hearing after vestibular schwannoma surgery is considered to remain stable even in long-term follow-up. Materials and Methods: Twenty-eight patients had preserved hearing after retrosigmoid suboccipital microsurgery of the vestibular schwannoma between 2008 and 2014. A standard audiological proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Other authors found that serviceable hearing (grade A or B) was preserved in 70.4% of patients [ 15 ]. Unfortunately, this preservation of acoustic function could deteriorate with time [ 16 , 17 ]. In our study, 55 patients (91%) presented with hearing deficits after surgery, grade D hearing loss occurring in 42 patients (70%), grade C in 11 patients (18.33%), grade B in 2 patients (3.33%).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors found that serviceable hearing (grade A or B) was preserved in 70.4% of patients [ 15 ]. Unfortunately, this preservation of acoustic function could deteriorate with time [ 16 , 17 ]. In our study, 55 patients (91%) presented with hearing deficits after surgery, grade D hearing loss occurring in 42 patients (70%), grade C in 11 patients (18.33%), grade B in 2 patients (3.33%).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the uncertainty of the growth trend of VS and the vari-ability of patients' symptoms (4), the decisions regarding surgical timing as well as surgical approach are difficult to make. Although some previous studies have demonstrated that preoperative hearing, tumor size, cerebrospinal fluid between the lateral tumor margin and the fundus of the internal auditory canal (IAC), and so on seem to be related to postoperative hearing preservation (HP) (5)(6)(7), other different results have been reported continuously (8). In short, there is a lack of an accurate prediction system and clinical decision-making strategy that takes cochlear nerve function preservation as the primary consideration.…”
Section: Introductionmentioning
confidence: 99%